2020
DOI: 10.21203/rs.3.rs-31117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal and neonatal outcomes of placenta previa with and without coverage of a uterine scar: A retrospective cohort study in a tertiary hospital

Abstract: Background To compare the maternal and neonatal outcomes of placenta previa (PP) with and without coverage of a uterine scar in Foshan, China. Methods A retrospective cohort study comparing all singleton pregnancies with PP was conducted at a tertiary, university-affiliated medical center from 1 January 2012 to 31 April 2017 in Foshan, China. Demographic, clinical and laboratory data were extracted from electronic medical records. Maternal and neonatal outcomes of PP with and without coverage of a uterine sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…18 In our study, a low APGAR score was observed in 25.85% of neonates. Low APGAR frequency was 15.2% in a similar study conducted by Rao J et al 19 Low birth weight was found to be 35.75% in our study. It was observed in our study that most of the babies (59.61%) with low birth weight had a low 5minute APGAR score.…”
Section: Discussionsupporting
confidence: 81%
“…18 In our study, a low APGAR score was observed in 25.85% of neonates. Low APGAR frequency was 15.2% in a similar study conducted by Rao J et al 19 Low birth weight was found to be 35.75% in our study. It was observed in our study that most of the babies (59.61%) with low birth weight had a low 5minute APGAR score.…”
Section: Discussionsupporting
confidence: 81%